Investigating the Relationship between Electrolyte Levels and ABO Blood Groups: Prospects for Customized Medicine - Airhomwanbor K. O.; Ebaluegbeifoh L. O.; Omolumen L. E.; Usiobeigbe O. S.; Ugege C.; Omisakin I. A.; Dada F. L.; Oikerhe E. G.; Imasete H. (Archives of Current Research International, 2024)
Human ABO blood type antigens exhibit alternative phenotypes and genetically derived glycoconjugate structures that are located on the red cell surface which play an active role in the cells' physiology and pathology. This study was carried out to evaluate the electrolytes, urea and creatinine of individuals with different ABO blood groups in Ekpoma. A total of one hundred (100) samples were used in this study. Electrolytes was estimated using ion selective electrode, urea was estimated using Berthelot method, while creatinine was estimated using Jaffe’s method. The results were presented in tables as mean ± standard deviation. Statistical analysis was done using one-way analysis of variance (ANOVA) and the student’s t-test. Significant difference was accepted at p<0.05. The results obtained showed that Sodium (Na) (mmol/L) was significantly higher (p<0.05) in subjects with blood group O (136.72±1.22) and blood group A (136.00±1.36) when compared with blood group B (134.56±2.56). Potassium (K) (mmol/L) was non-significantly higher (p>0.05) in blood group A (3.62±0.29), followed by blood group O (3.59±0.18) and least in blood group B (3.51±0.22). Bicarbonate (HCO3) (mmol/L) was non-significantly higher (p>0.05) in blood group A (21.17±1.76), followed by blood group O (20.67±1.09) and least in blood group B (20.52±0.91). Chloride (Cl) (mmol/L) was non-significantly higher in blood group O (103.20±1.81) followed by blood group A (102.10±2.35) and least in blood group B (101.60±3.58). Furthermore, Urea (mg/dl) was non-significantly higher (p>0.05) in blood group O (23.20±4.57), followed by blood group A (21.48±4.15) and least in blood group B (20.76±5.15). Similarly, Creatinine (mg/dl) was non-significantly higher in blood group O (0.65±0.15), followed by blood group A (0.63±0.12) and least in blood group B (0.62±0.15). In conclusion, electrolytes, urea and creatinine were higher in blood group A and O compared with blood group B. With respect to gender, Na, HCO3, Cl, Urea and Creatinine were significantly higher in male subjects compared with female subjects. There was no significant difference in electrolytes, urea and creatinine of the subjects with respect to age (p>0.05). Further studies should be carried out to understand the mechanism behind increase in electrolytes, urea and creatinine in certain blood group compared with others.